Raso Banagari: Ekspresi Sosial Perantau terhadap Pembangunan Kampung Halaman - Syamsurizaldi, Syamsurizaldi; Putri, Annisa Aulia; Sari, Miftahul Viona; Yoliandri, Ridho (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2020)
Generally, emigrants have a deep interest in the condition of their hometown. In the Minang community, that sense is called